Formal and Non-Formal Development of Children as Criminal Offenders in Juvenile Correctional Institutions - Irsan, Meydisa (Formosa Journal of Multidisciplinary Research, 2024)
The problem in this study is how the implementation of formal and non-formal coaching for children as perpetrators of criminal acts in the Special Development Institute for Children Klas II Bandar Lampung and what factors hinder the implementation of formal and non-formal coaching for children as perpetrators of criminal acts in the Special Development Institute for Children Klas II Lampung. The problem approach that will be used in this research is normative juridical and empirical juridical, the sources in the research are the Head of LPKA, LPKA Lampung Officers and Correctional Students of LPKA Lampung. The results showed that the process of implementing formal and non-formal coaching for children as perpetrators of criminal acts in the Special Development Institute for Children Klas II Bandar Lampung has been carried out even though it has not been maximised, it can be seen from the formal coaching that runs quite well where formal coaching is given from the elementary school level, junior high school and high school education levels. While non-formal coaching has not been running optimally marked by the decline in correctional students who take part in skills training programmes.